Meningkatkan Nilai Karakter Pada Siswa Sekolah Dasar dengan Melestarikan Budaya Gendang Beleq Berbasis Tri Hita Karana - Fazalani, Runi; Sutajaya, I Made; Suja, I Wayan (LPPM Institut Pendidikan Nusantara Global, 2024)
Education with low character causes a crisis of national identity among the younger generation. The purpose of this article is an attempt to improve. The method used in the article is to conduct a literature review of various previous studies (literature review). The purpose of writing this article is to analyze various relevant theories, the literature used is research or reviews that have existed in scientific works and are published in journals. The result of this research is implementing Tri Hita Karana in schools through the implementation of Education and Training (Soft Skills and Entrepreneurship) with a cultural content and encouraging students to always explore the knowledge and skills of successful people and collaborate with people who have great intelligence, guide and invites students to have faith and act exemplary by always living cleanly and keeping the environment clean. Implementing Tri Hita Karana in schools through the provision of Education and Training (Soft Skills and Entrepreneurship) with a cultural content and encouraging students to always explore the knowledge and skills of successful people and collaborate with people who have great intelligence, guiding and inviting students to believe and act exemplary by always living cleanly and keeping the environment clean.